Identification of DVA Interneuron Regulatory Sequences in Caenorhabditis elegans - Puckett Robinson, Carmie (Public Library of Science, 2013)

(untitled)
BACKGROUND: The identity of each neuron is determined by the expression of a distinct group of genes comprising its terminal gene battery. The regulatory sequences that control the expression of such terminal gene batteries in individual neurons is largely unknown. The existence of a complete genome sequence for C. elegans and draft genomes of other nematodes let us use comparative genomics to identify regulatory sequences directing expression in the DVA interneuron. METHODOLOGY/PRINCIPAL FINDINGS: Using phylogenetic comparisons of multiple Caenorhabditis species, we identified conserved non-coding sequences in 3 of 10 genes (fax-1, nmr-1, and twk-16) that direct expression of reporter transgenes in DVA and other neurons. The conserved region and flanking sequences in an 85-bp intronic region of the twk-16 gene directs highly restricted expression in DVA. Mutagenesis of this 85 bp region shows that it has at least four regions. The central 53 bp region contains a 29 bp region that represses expression and a 24 bp region that drives broad neuronal expression. Two short flanking regions restrict expression of the twk-16 gene to DVA. A shared GA-rich motif was identified in three of these genes but had opposite effects on expression when mutated in the nmr-1 and twk-16 DVA regulatory elements. CONCLUSIONS/SIGNIFICANCE: We identified by multi-species conservation regulatory regions within three genes that direct expression in the DVA neuron. We identified four contiguous regions of sequence of the twk-16 gene enhancer with positive and negative effects on expression, which combined to restrict expression to the DVA neuron. For this neuron a single binding site may thus not achieve sufficient specificity for cell specific expression. One of the positive elements, an 8-bp sequence required for expression was identified in silico by sequence comparisons of seven nematode species, demonstrating the potential resolution of expanded multi-species phylogenetic comparisons.